Comprehensive study of the phenolic composition of the edible parts of jambolan fruit (Syzygium cumini (L.) Skeels). (April 2016) - Tavares, Iasnaia Maria de Carvalho; Lago-Vanzela, Ellen Silva; Rebello, Ligia Portugal Gomes; Ramos, Afonso Mota; Gómez-Alonso, Sergio; García-Romero, Esteban; Da-Silva, Roberto; Hermosín-Gutiérrez, Isidro
Abstract: Jambolan fruit has been used in traditional Indian medicine and has recently attracted interest as a functional food. The comprehensive study by HPLC–DAD-ESI-MS/MS has revealed the occurrence of around 74 individual phenolic compounds in the edible parts of jambolan, including 9 anthocyanins (mainly based on delphinidin, petunidin and malvidin), 9 flavonols (myricetin, laricitrin and syringetin glycosides), 19 flavanonols (dihexosides of dihydromyricetin and its methylated derivatives), 8 flavan-3-ol monomers (mainly gallocatechin), 13 gallotanins and 13 ellagitanins, together with some proanthocyanidins (highly galloylated prodelphinidins) and free gallic and ellagic acids. No hydroxycinnamic acid derivatives were detected. The skin of the jambolan fruit accumulated great amounts of phenolic compounds, almost all of the non-tannin phenolics. In contrast, condensed tannins (proanthocyanidins) and hydrolyzable tannins (gallotannins and ellagitannins) were present in both edible parts, accounting for greater amounts in the skin. Overall, the main phenolics of jambolan were anthocyanins and hydrolyzable tannins (similar amounts of gallotannins and ellagitanins), followed by flavanonols, flavonols and flavan-3-ols. Highlights: 74 individual phenolics found in the edible parts of jambolan, mainly in the skin Anthocyanins, gallotannins and ellagitannins are the main phenolics. High amounts of flavanonols are also found in jambolan. Jambolan flavonols derived from myricetin, laricitrin and syringetin Condensed tannins are minor phenolics and hydroxycinnamates were not found.